Diet of tropical insectivorous birds in lowland Malaysian rainforest - Mansor, Mohammad Saiful; Abdullah, Nurul Ashikin; Abdullah Halim, Muhammad Rasul; Nor, Shukor Md; Ramli, Rosli (Taylor & Francis, 2018)
Despite the importance of diet in avian ecology, knowledge of bird diet in tropical regions, particularly South-East Asia, is limited. Assessing predator–prey relationships of how energy flows across ecosystems provides insight into niche segregation of sympatric species. We examined induced-regurgitation samples from 15 species of insectivorous birds – 12 babblers and three flycatcher-like species – from the Krau Wildlife Reserve, central Peninsular Malaysia. The main objective of this study was to compare and characterise the diet of similar trophically insectivorous birds so as to examine the occurrence of dietary overlap or segregation. The majority of identified prey items belong to the following arthropod taxa: Coleoptera (53%), Hymenoptera (19%), Blattodea (11%), and Araneae (11%). The diet of all bird species slightly overlapped (p = 0.070) but network analysis yielded a relatively low value (R o = 0.53), indicating dietary divergence may have occurred among the studied bird species, possibly reflected by the variation in proportion of arthropod groups. A high proportion of Coleoptera and three other arthropod groups (i.e. Hymenoptera, Blattodea and Araneae) in the diet of studied birds could be related to their richness and abundance in aerial leaf-litter, the substrate preferred by most babblers. Dietary differences may further be explained by variations in bill shapes and sizes, likely corresponding to prey size. Unique foraging strategies (utilising different vertical strata, microha-bitats, and attack manoeuvres) could also lead to dietary separation among sympatric species. Flycatcher-like species were expected to flycatch different prey items (families or lower taxa) versus the gleaning birds (most babblers). This study successfully discerned more details on the diets of insectivorous birds inhabiting Malaysian forests, providing a foundation for future studies on the ecology and biology of understorey birds.